Marshall-Lerner condition for South Asia: A panel study analysis - Adnan Ali Shahzad; Bilal Nafees; Nazar Farid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
Fluctuations in exchange rate have threatened the stability of global financial system and have invited unwarranted currency war. South Asia has been experiencing a whopping trade deficit from the last many years. This study is an attempt to analyze the impact of exchange rate depreciation on trade balance by estimating Marshall-Lerner condition for South Asian countries. This study used the panel data of seven South Asian countries consisting of Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan and Sri-Lanka for the period of 1993 to 2010. The study used random effects model (REM) to estimate the import and export demand elasticity. The study used Hausman Specification test to make a choice between fixed effects model and random effects model. The study has also used Breusch-Pagan test to make a choice between random effect model and simple panel ordinary least square model. The study finds that sum of import and export demand elasticity is less than one for South Asian countries, M-L condition does not fulfill, and that is why no improvement in trade balance has been seen in response to exchange rate depreciation. Moreover, the results suggest that some relevant policies like, export promotion measures and industrialization of import substitution must be taken into consideration to improve the trade balance. The study also suggested some future research directions at the end.
Keywords: 330; Marshall-Lerner condition; exchange rate; trade balance; export and import demand elasticity; random effect model; south Asia